Global Health Law - Gostin, Lawrence O. (Harvard University Press, 2014)
The international community has made great progress in improving global health. But staggering health inequalities between rich and poor still remain, raising fundamental questions of social justice. In a book that systematically defines the burgeoning field of global health law, Lawrence Gostin drives home the need for effective global governance for health and offers a blueprint for reform, based on the principle that the opportunity to live a healthy life is a basic human right. Gostin shows how critical it is for institutions and international agreements to focus not only on illness but also on the essential conditions that enable people to stay healthy throughout their lifespan: nutrition, clean water, mosquito control, and tobacco reduction. Policies that shape agriculture, trade, and the environment have long-term impacts on health, and Gostin proposes major reforms of global health institutions and governments to ensure better coordination, more transparency, and accountability. He illustrates the power of global health law with case studies on AIDS, influenza, tobacco, and health worker migration. Today's pressing health needs worldwide are a problem not only for the medical profession but also for all concerned citizens. Designed with the beginning student, advanced researcher, and informed public in mind, Global Health Law will be a foundational resource for teaching, advocacy, and public discourse in global health